1988
DOI: 10.1002/j.1556-6676.1988.tb00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Premature Termination from University Counseling Centers: A Review

Abstract: Many clients leave counseling prematurely (i.e., without their counselors' agreement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 44 publications
(96 reference statements)
0
30
0
Order By: Relevance
“…They reported that only 71 %of the adult clients in a seven-session career counseling workshop attended fiveor more sessions. Although noncompletion ofother forms ofcounseling in college counseling centers and community agencies is widespread and has been studied extensively (Howard, Kopta, Krause,& Orlinsky,1986;Mennicke, Lent, & Burgoyne, 1988), it is surprising that it has not received more attention in the literature on career counseling. Nonuse ofallotted counseling and assessment hours is also likely to concern counselors in university extension centers because high attrition from some of their programs may imperil their state funding.…”
mentioning
confidence: 99%
“…They reported that only 71 %of the adult clients in a seven-session career counseling workshop attended fiveor more sessions. Although noncompletion ofother forms ofcounseling in college counseling centers and community agencies is widespread and has been studied extensively (Howard, Kopta, Krause,& Orlinsky,1986;Mennicke, Lent, & Burgoyne, 1988), it is surprising that it has not received more attention in the literature on career counseling. Nonuse ofallotted counseling and assessment hours is also likely to concern counselors in university extension centers because high attrition from some of their programs may imperil their state funding.…”
mentioning
confidence: 99%
“…For example, the ICB may be useful when examining the relationship between countertransference behavior and variables such as working alliance (e.g., Bordin, 1979), internal working models (e.g., Lopez, Melendez, Sauer, Berger, & Wyssmann, 1998), the real relationship (e.g., Gelso & Hayes, 1998), or premature termination (e.g., Mennicke, Lent, & Burgoyne, 1988). If a therapist exhibits countertransference behavior in a session, how able is she or he to establish a working alliance or to be genuine and reality based with the client?…”
Section: Discussionmentioning
confidence: 99%
“…It is a unilateral client decision to withdraw prior to reaching therapeutic goals (Allgood, Parham, Salts, & Smith, p. 195, 1995;Rainer & Campbell, p. 19, 2001;Smith, Subich, & Kolander, 1995). Other terms used in the literature to identify this form of termination are unilateral termination, discontinuing, drop out (Prochaska & DiClemente, 1994;Pekarik, 1992b;Wierzbicki & Pekarik, 1993;Rainer & Campbell, p. 19, 2001), unplanned terminations, premature termination (Allgood, Parham, Salts, & Smith, 1995), and attrition (Mennicke, Lent, & Burgoyne, 1988;Hunt & Andrews, 1992). A problem encountered in making sense of the literature is a lack of consensus or consistency on an operational definition of any of the preceding terms (Pekarik, p. 86, 1985a).…”
Section: Client-initiated Terminationmentioning
confidence: 97%